2017
DOI: 10.3390/beverages3010005
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Aging of the Traditional Greek Distillate Tsipouro Using Wooden Chips. Part I: Effect of Static Maceration vs. Ultrasonication on the Polyphenol Extraction and Antioxidant Activity

Abstract: Abstract:The Greek traditional grape marc distillate Tsipouro was subjected to accelerated aging, using wooden chips from acacia, cherry, chestnut and oak wood. The processes included treatments under static maceration and ultrasonication and the evolution of the total polyphenol concentration was monitored over a period of 30 days. During this period, leaching of polyphenols from the chips into the distillate was found to obey first-order kinetics, but no statistical differences were shown between the two tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Despite how the aging method is reformed or is innovative, the use of wood is indispensable and is the key to ensuring the unique flavor of distilled beverages. Therefore, the use of alternative wood and botanical species (Canas et al, 2009;Coldea et al, 2020) or stainless tanks with wooden fragments (Caldeira et al, 2017), combined with micro-oxidation Granja-Soares et al, 2020) and other physical techniques (Anjos et al, 2020; Taloumi good as that long-term barrel-aged spirits Balcerek et al, 2017;Caldeira et al, 2017;Canas et al, 2016;Giannakourou et al, 2018;Granados et al, 2002 Wood fragments & Makris, 2017, are potential substitutes for traditional oak barrel aging. Pottery jars do not provide flavor components to the distilled beverage; they mainly aid in the chemical transformations between components.…”
Section: Alternative Aging Systemsmentioning
confidence: 99%
“…Despite how the aging method is reformed or is innovative, the use of wood is indispensable and is the key to ensuring the unique flavor of distilled beverages. Therefore, the use of alternative wood and botanical species (Canas et al, 2009;Coldea et al, 2020) or stainless tanks with wooden fragments (Caldeira et al, 2017), combined with micro-oxidation Granja-Soares et al, 2020) and other physical techniques (Anjos et al, 2020; Taloumi good as that long-term barrel-aged spirits Balcerek et al, 2017;Caldeira et al, 2017;Canas et al, 2016;Giannakourou et al, 2018;Granados et al, 2002 Wood fragments & Makris, 2017, are potential substitutes for traditional oak barrel aging. Pottery jars do not provide flavor components to the distilled beverage; they mainly aid in the chemical transformations between components.…”
Section: Alternative Aging Systemsmentioning
confidence: 99%
“…Ultrasonication and static maceration (SM) have also been exploited to speed-up aging in Greek traditional grape marc distillate Tsipouro (Taloumi & Makris, 2017). In addition, acacia, cherry, chestnut, and oak wood chips were essential to facilitate this process further.…”
Section: Applications In Spiritsmentioning
confidence: 99%
“…In the last years, alternative ageing processes have been studied, namely the application of wood fragments to the spirits kept in stainless steel tanks. These studies were focused on cider spirits [16], apple spirit [17], grape marc spirits [18,19], and sugar cane spirits [20,21]. Concerning the wine spirits, the research revealed that the fragment size/shape and the kind of wood had a significant effect on the chemical composition of these beverages [8,22,23].…”
Section: Of 15mentioning
confidence: 99%